Composition of the Essential Oil of Pistachia khinjuk Fruits Grown in Ilam Province of Iran - Gharib Naseri, Nahid; Ashnagar, Alamdar; Husseini, Shanaz (Asian Journal of Chemistry, 2010)
The essential oil obtained from the fruits (whole seeds, kernel and the green hull of the seeds) of Pistachia khinjuk tree growing wild in Ilam province of Iran was analyzed by GC-MS. Thirty-four compounds consisting ca. 99% of the total components were identified in the oil which was obtained in 4.0% (v/w). Among them, cis-ocimene (24%), α-pinene (17.9%), myrcene (14%) and trans-ocimene (8%) were the major components.